2021
DOI: 10.1002/pro.4028
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro structure and functions of the disordered late embryogenesis abundant three proteins

Abstract: Late embryogenesis abundant (LEA) proteins are produced during seed embryogenesis and in vegetative tissue in response to various abiotic stressors. A correlation has been established between LEA expression and stress tolerance, yet their precise biochemical mechanism remains elusive. LEA proteins are very rich in hydrophilic amino acids, and they have been found to be intrinsically disordered proteins (IDPs) in vitro. Here, we perform biochemical and structural analyses of the four LEA3 proteins from Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…As LEA proteins have unique biochemical properties, such as high hydrophilicity [ 21 ], presence of a large number of charged amino acid (AA) residues [ 22 ], glycine, or other tiny AAs [ 23 ], small number of cysteine residues [ 24 ], and a lack of tryptophan residues [ 7 ], they are tolerant to heat and acid and participate in numerous physiological processes associated with plant development and responses to adversity, thereby contributing to various stress tolerance responses [ 7 , 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As LEA proteins have unique biochemical properties, such as high hydrophilicity [ 21 ], presence of a large number of charged amino acid (AA) residues [ 22 ], glycine, or other tiny AAs [ 23 ], small number of cysteine residues [ 24 ], and a lack of tryptophan residues [ 7 ], they are tolerant to heat and acid and participate in numerous physiological processes associated with plant development and responses to adversity, thereby contributing to various stress tolerance responses [ 7 , 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…After decades of research, it is believed that G3LEA proteins could mitigate ROS damage and participate in environmental stress, such as drying [ 33 , 34 , 35 , 36 ], salinity [ 34 , 37 ], oxidation [ 35 ] and freezing [ 38 ]. More and more researches have indicated that G3LEA proteins not only existed in plants, but also in many prokaryotes acting in a chaperone-like manner [ 39 , 40 ], for example, DosH, which is characterized by an intrinsically ordered secondary structure from D. radiodurans R1.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that plant IDPs (mainly LEA proteins) are able to protect lactate dehydrogenase enzyme activity against damage caused by desiccation, heat stress, or freezing and thawing cycles [59,[68][69][70][71][72][73][74][75][76]. The disorder and flexibility structure of LEA proteins may allow them to act as a kind of "molecular shield", forming a physical barrier between neighbouring macromolecules and preventing their aggregation and inactivation under stress conditions [77].…”
Section: Molecular Shielding For Enzyme Protectionmentioning
confidence: 99%